On the Effectiveness of Feed-in Tariffs in the Development of Photovoltaic Solar - Elbert Dijkgraaf; Tom van Dorp; Emiel Maasland (Tinbergen Institute, 2014)
Growing concern for climate change and rising scarcity of fossil fuels prompted governments to stimulate the development of renewables. This paper empirically tests whether feed-in tariff (FIT) policies have been effective in the development of photovoltaic solar (PV), explicitly taking into account structure and consistency of FITs. Panel data estimations are employed for 30 OECD member countries over the period 1990-2011. We find a positive effect of the presence of a FIT and the development of a countrys share of PV in the electricity-mix. This effect increases if policies are consistent. Tariff height is the most important characteristic of a FIT, but other characteristics such as cost level, duration of contract and restrictions on capacity levels can also not be neglected if the goal is to increase effectiveness of FITs.
Keywords: C23; G11; H23; N70; Q42; Q48; 330; Photovoltaic solar; Feed-in tariffs; Policy-consistency; Design characteristics